INACTIVACION DEL BACTERIOFAGO DE RHIZOBIUM MELILOTI POR BACTERIAS AEROBIAS ESAN LUIS POTOSIORULADAS - GUERRERO, DELIA; CASAS CAMPILLO, CARLOS (Instituto de Salubridad y Enfermedades Tropicales, CD MEXICO, DF, MEX, 1949)
The effect of an organic soil fraction (petroleum ether soluble) upon the growth of R meliloti and R japonicum was studied in liquid cultures As a rule, amts ranging 20-100 R meliloti units per 16 ml of the liquid culture showed bacteriostatic or ba
CIENC MEX
Keywords: INACTIVACION, BACTERIOFAGO, RHIZOBIUM MELILOTI, BACTERIAS AEROBIAS ESPORULADAS; MULTIDISCIPLINARIA; MICROBIOLOGIA; BACTERIOLOGIA